1968
DOI: 10.1084/jem.128.5.959
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactions Among Group a Streptococci

Abstract: Strains of four streptococcal types, 33, 41, 43, 52, and a nontypable strain, Ross, cross-reacted in precipitin and bactericidal tests. The homologous reactions, which determined the type, afforded the major protection and developed promptly and regularly in the serum of rabbits during immunization. The associated cross-reactions, on the other hand, appeared in the serum of certain rabbits only, were often not as strong as the associated homologous reactions, and required for their presence a longer period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…the inability to grow aero-bically on routine sheep blood agar) permitted separate analysis of these two strains. The finding that the 'other pyoderma strain' showed precipitation reactions with both types 41 and 43 M antisera is of interest in view of the recent report by Wiley & Bruno (1968) which describes precipitin and bactericidal crossreactions between types 33, 41, 43, 52 and Ross. This strain apparently has many of the characteristics of the Ross strain, but the exact nature of the precipitation reactions and possible interrelationships of these two strains will await more detailed studies.…”
Section: Discussionmentioning
confidence: 97%
“…the inability to grow aero-bically on routine sheep blood agar) permitted separate analysis of these two strains. The finding that the 'other pyoderma strain' showed precipitation reactions with both types 41 and 43 M antisera is of interest in view of the recent report by Wiley & Bruno (1968) which describes precipitin and bactericidal crossreactions between types 33, 41, 43, 52 and Ross. This strain apparently has many of the characteristics of the Ross strain, but the exact nature of the precipitation reactions and possible interrelationships of these two strains will await more detailed studies.…”
Section: Discussionmentioning
confidence: 97%
“…Wiley and Wilson (26) later reported the occurrence of 2 M antigens on the surface of certain strains of type 14 organisms. Other similar studies reported cross-protective immune responses evoked by various antigen preparations (27,28). We now recognize that some M proteins contain cross-protective and typespecific epitopes (29).…”
Section: Discussionmentioning
confidence: 99%